An Automatic Device for Testing Medical Electrodes - Avdeeva D. K. Diana Konstantinovna; Vylegzhanin O. N. Oleg Nikolaevich; Grekhov I. S.; Kazakov V. Yu. Veniamin Yurevich; Kim V. L. Valery Lvovich; Klubovich I. A. Inna Alekseevna; Rybalka S. A. Sergey Anatolyevich; Sadovnikov Yu. G. Yuri Georgievich; Yakimov E. V. Evgeny Valeryevich (2009, 2009)
Title screen